QSAR Studies of 2-Phenoxyacetamide Analogues, a Novel Class of Potent and Selective Monoamine Oxidase Inhibitors - Ashish Kumar Singh; Jyoti Patel; Nimisha Jain; Pradeep Kumar Singour (Current Research in Pharmaceutical Sciences, 2018)
The primary objective of this investigation was to develop a QSAR model for novel series of phenoxy acetamide derivatives as Monoamine Oxidase Inhibitors. The data series were taken from the reported work of Wei Shen et al., 2014. The selected series consists of total 20  compounds, divided into two sets training set having 18 compounds and test set with 2 compounds. All the structures of phenoxy acetamide derivatives were sketched using Chem Office 2001. QSAR models were obtained by using VALSTAT software. The best-developed model showed a good correlative and predictive ability having regression coefficient (r2) of 0.9033 and q2 is 0.8376. For MAO B inhibitor activity, MW has positively correlated. The positive correlation of MW indicates that bulky group or higher molecular weight compounds are important for better MAO enzymes inhibition activity. The negative correlation of HOMO indicated that electrophilic group may increase the activity. The BetaPol also negatively correlated indicated less polar group give more activity. Based on the developed QSAR model, it may be concluded that highest occupied molecular orbital (HOMO) energy, molecular weight and Beta Polarizability are to be considered while designing newer compounds, for their potential MAO inhibitory activity.